MicroRNA390 Is Involved in Cadmium Tolerance and Accumulation in Rice - Ding, Yanfei; Ye, Yaoyao; Jiang, Zhihua; Wang, Yi; Zhu, Cheng (Frontiers in Plant Science, 2016)
Cadmium (Cd) is a non-essential heavy metal that is toxic to plants. microRNAs (miRNAs) are 21-nucleotide RNAs that are ubiquitous regulators of gene expression at the post-transcriptional level. Several plant miRNAs, such as miR390, have vital roles in plant growth, development and responses to environmental stresses including heavy metal stress. In this study, the expression of mature miR390 was significantly down-regulated under Cd stress in rice. Consequently, the target gene of miR390, OsSRK was dramatically induced by Cd treatment. Transgenic rice plants overexpressing miR390 displayed reduced Cd tolerance and higher Cd accumulation compared with wild-type plants. Simultaneously, expression of OsSRK was less pronounced in 35S:MIR390 plants than in wild-type. These results indicate that miR390 was a negative regulator involved in Cd stress tolerance in rice.